Calcification in masseter muscle: A case report - R, Sanjana; C, Poornima; P, Balaji; MB, Sowbhagya (Indian Journal of Case Reports, 2017)
Biomineralization is a process by which living organisms produce minerals, often to harden the existing tissues. Defect in biomineralization occurring in soft tissues is defined as ectopic calcification. Dystrophic calcification is one of the types of ectopic calcifications. This soft tissue mineralization may develop in a wide variety of unrelated disorders and degenerative processes. It can occur in all soft tissues but cardiovascular tissues are particularly prone to calcification. Calcification in an isolated muscle like the masseter is rare, its pre-operative diagnosis pose a challenge in view of differential diagnosis. Here, we report a 55-year-old male who presented with swelling over right middle third of the face. Meticulous examination and selection of suitable investigations have helped us to arrive at an appropriate diagnosis.